Grid code compatibility and real-time performance analysis of an efficient inverter topology for PV-based microgrid applications. (June 2021) - Ghaderi, Davood; Bayrak, Gökay; Guerrero, Josep M.
Highlights: The proposed inverter is minimizing the leakage current, and increases efficiency. The power losses are lower than popular topologies such as H5, H6 and HERIC inverters. The voltage stresses of the switches are reduced. These features are due to the formation of a suitable freewheeling path. The freewheeling path separates the ac section from the DC side. Abstract: The integration of the Photovoltaic (PV) - based Distributed Generation (DG) Systems to the conventional electrical grid is a significant issue to achieve a confidential grid operation. This study presents a novel structure for the suppression of the common-state leakage current for PV-based inverters. It investigates the real-time performance of the inverter for the grid-code compatibility of the PV-based microgrid applications. Many of the topologies have been introduced to suppress leakage currents in grid-based Photovoltaic (PV) inverters, but most of them cannot practically reach more than 95% efficiency. The number of the components, especially the switching semiconductors, including the power switches and power diodes and the current and ripples' level in the topology filter side inductors, are essential criteria for efficiency. The proposed inverter includes six power switches and two power diodes. Since different operational states, only two power components per branch of the inverter are activated a higher efficiency than the conventional H5, H6, and HERIC converters. It presents the THD equal to 1, 42 for load-connection states that is considerable. This converter can also generate pure sinusoidal current and voltage waveforms for the reactive loads, especially resistive-inductive load connections that are most common in industrial applications. As a study-case, the implemented inverter was tested under different grid conditions in the laboratory, and a real-time LabVIEW-based monitoring and grid protection system was realized within the research scope. Under/over-frequency protection and under/over voltage protection were performed to provide a reliable microgrid management system for the developed inverter. According to IEEE 929-2000 threshold values for the breakers' reaction operation under the ±10% as the output threshold voltage, the converter's performance is presented. A real-time monitoring and protection system are developed, and the developed LabVIEW analyzer has done the hardware test results. THD and spectrum analysis are also investigated in the real-time domain by the developed inverter test system. In this way, the implemented inverter's grid code compatibility is investigated in real-time, and the experimental results show that the proposed inverter is reliable for PV-based microgrid applications.